A Determination of The Best Employees using Simple Additive Weighting (SAW) Method - Retnasari, Tri; Prihatin, Titin; Fikri, Muhammad (Sinkron : jurnal dan penelitian teknik informatika, 2019)
The most important part of a company is employees. Management of human resources (HR) from each company is very influential in the many aspects that determine the success of the work of the company itself. One of the most important things in the management of a company to improve employee performance is to do the best selection of employees periodically so as to produce an attitude of dedication to the company. Therefore, this study tries to choose the best employees at PT. Buana Estate Agrowisata Villa Bukit Hambalang uses a simple additive weighting (SAW) method, which consists of five criteria namely attendance, performance, discipline, attitude and tidiness. The sampling is employees who are at PT. Buana Estate Agrowisata Villa Bukit Hambalang. This study got a result of the number of employees as many as 25 employees who were used as research samples, employees named Pathurochman got the biggest score of 0.95 and received the title of best employee at PT. Buana Estate Agrowisata Villa Bukit Hambalang.